2017
DOI: 10.1007/s10393-017-1285-2
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Stakeholder Analysis of Avian Influenza Policy in Bangladesh

Abstract: Avian influenza is a major animal and public health concern in Bangladesh. A decade after development and implementation of the first national avian influenza and human pandemic influenza preparedness and response plan in Bangladesh, a two-stage qualitative stakeholder analysis was performed in relation to the policy development process and the actual policy. This study specifically aimed to identify the future policy options to prevent and control avian influenza and other poultry-related zoonotic diseases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Private and public sectors were equally important in controlling poultry diseases including AI at country and farm level. These stakeholders could be targeted to inform policy making and develop robust approaches for disease control (35). The study revealed limited coordination between private and public sector stakeholders providing health services.…”
Section: Discussionmentioning
confidence: 99%
“…Private and public sectors were equally important in controlling poultry diseases including AI at country and farm level. These stakeholders could be targeted to inform policy making and develop robust approaches for disease control (35). The study revealed limited coordination between private and public sector stakeholders providing health services.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average number of reported poultry outbreaks is declining in Bangladesh, that is from 83 and 10 outbreaks in commercial and backyard poultry in 2007–2012, to 2 and 0 respectively, in 2013–2019 (DLS, 2019). Underreporting might be one reason for this decline as compensation policies were discontinued (Chattopadhyay et al., 2018) or because farmers might have accepted the ubiquity of HPAI outbreak occurrence similar to the endemicity of Newcastle Disease in many developing countries (Spradbrow, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Underreporting might be one reason for this decline as compensation policies were discontinued (Chattopadhyay et al, 2018) or because farmers might have accepted the ubiquity of HPAI outbreak occurrence similar to the endemicity of Newcastle Disease in many developing countries (Spradbrow, 1996).…”
mentioning
confidence: 99%
“…This will enable and encourage ongoing multi-sectoral collaboration among animal health, human health and environmental health experts to be strengthened towards ensuring that the health benefits for all species would be considered. These would help to prevent and control the spread of poultry origin zoonotic diseases in Bangladesh (Chattopadhyay et al, 2018). These findings place an emphasis on public-private partnership towards the sustainable control of the disease, and the gradual phasing out of LPMs would then be recognized as a long-term goal.…”
Section: Likelihood Of Unexpected Impacts In Relation To Livelihoodmentioning
confidence: 99%